Given

#color(white)("XXX")color(green)((x-2)^2)+color(blue)((-x+6)^2)=color(brown)(32)#

Expanding the left side

#color(white)("XXX")color(green)(x^2-4x+4)+color(blue)(x^2-12x+36)=color(brown)(32)#

Combining like terms

#color(white)("XXX")2x^2-16x+40=color(brown)(32)#

Dividing both sides by #2# to simplify

#color(white)("XXX")x^2-8x+20=16#

Converting to standard quadratic form

#color(white)("XXX")color(red)1x^2color(magenta)(-8x)color(orange)(+4)=0#

With no obvious (at least to me) rational factors:

Apply the quadratic formula

#color(white)("XXX")x=(-color(magenta)b+-sqrt(color(magenta)b^2-4color(red)acolor(orange)c))/(2color(red)a)#

#color(white)("XXXXX")=(8+-sqrt(64-16))/2#

#color(white)("XXXXX")=4+-2sqrt(3)#